2009
DOI: 10.1590/s0036-46652009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Classic and molecular study of Giardia duodenalis in children from a daycare center in the region of Presidente Prudente, São Paulo, Brazil

Abstract: SUMMARYEpidemiological studies on giardiasis by using molecular techniques such as RAPD (Randomly Amplified Polymorphic DNA) may give information on factors related to the transmission of Giardia duodenalis. The aim of this work was to assess the epidemiology of G. duodenalis in 101 children attended at a daycare center in Presidente Bernardes, SP, Brazil. After parasitological examinations in feces samples, 15 children presented cysts of G. duodenalis. Their respective parents, brothers and pets, besides the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
1
7
0
2
Order By: Relevance
“…This may suggest that infection with Genotype B may not always lead to clinical symptoms. Prior exposure has been shown to confer some degree of protection to subsequent infections [ 30 , 31 ], and such cases may be reservoirs sustaining transmission to susceptible host, particularly at day-care centers, where children have frequent contact with each other [ 15 , 32 , 33 ]. Interestingly, our data is in contrast to a study by Opintan et al [ 22 ] who identified Cryptosporidium as the commonest cause of diarrhoea in children at PML but did not find any case of Giardiasis.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that infection with Genotype B may not always lead to clinical symptoms. Prior exposure has been shown to confer some degree of protection to subsequent infections [ 30 , 31 ], and such cases may be reservoirs sustaining transmission to susceptible host, particularly at day-care centers, where children have frequent contact with each other [ 15 , 32 , 33 ]. Interestingly, our data is in contrast to a study by Opintan et al [ 22 ] who identified Cryptosporidium as the commonest cause of diarrhoea in children at PML but did not find any case of Giardiasis.…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on a sample from an underprivileged population in which a high prevalence of giardiasis was largely observed when compared to studies done in other cities in Brazil 4,5,[7][8][9][10][11][12][13][16][17][18][19] . It is part of an "Extension Project to the Community" where two undergraduate students voluntarily worked on weekends, trying to make the community aware of the importance of health care.…”
Section: Discussionmentioning
confidence: 99%
“…High infection rates for giardiasis have been reported for developing countries, and some recent data are listed in Table 2. In various Asian countries (Bangladesh, Cambodia, China, India, Indonesia, Laos, Malaysia, Nepal, Philippines, Thailand, Turkey, Saudi Arabia, and Vietnam), North America (Cuba, Mexico, and Nicaragua), South America (Argentina, Brazil, Colombia, and Peru), and Africa (northern Africa, west Africa, and South Africa), most of the studies focused on children, and infection rates for G. duodenalis fell into the range of 8% to 30% in the majority of those studies (12,29,56,62,63,65,69,144,160,166,174,184,186,202,203,229,234,237,239,252,253,281). In a few studies, the infection rate was lower than 4% or higher than 30% (65,137,145,230,243,274,280).…”
Section: Public Health Importance Of Giardiasismentioning
confidence: 99%